Assessment of dental implant stability during healing period and determination of the factors that affect implant stability by means of resonance frequency analysis(Clinical study) - Ibraheem, Noor S; Al-Adili, Sahar S (Journal of Baghdad College of Dentistry, 2015)
Background: Implant stability is considered one of the most important factors affecting healing and successful osseointegration of dental implants. The aims of the study were to measure the implant stability quotient (ISQ) values during the healing period and to determine the factors that affect implant stability.Materials and methods: Thirty patients enrolled in the study (17 female, 13 male). They received 44 ImplantiumÂ® Dental Implants located as the following: 22 implants in maxillary jaw, 22 implants in mandibular jaw from them 17 implants in anterior segment and 27 in posterior segment. The bone density determined using interactive CT scan and classified according to the Misch bone density classification (29 implants in (D3), 15 implants in (D4)). Resonance frequency analysis was used for direct measurement of implant stability on the day of implant placement and 8, 16 and 24 weeks after implant placement. Results: The lowest mean of average ISQ was at the 8th week (69.5) and then the mean increased to reach at the 24th week (76.8). Mandibular implants showed significantly higher ISQ values than maxillary implants. Implants placed in the posterior segment of the jaw had significantly higher ISQ values than implants in the anterior segment. A significant, positive linear correlation was observed between the implant diameter and the implant stability (r=0.343 p